2022
DOI: 10.3390/children9060925
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Health Literacy in Relation to Their BMI z-Score, Food Intake, and Physical Activity: A Cross-Sectional Study among 8–11-Year-Old Children in The Netherlands

Abstract: Overweight and obesity in children are an increasing public health problem. Health literacy (HL) is a determinant of obesity and body mass index (BMI) rates in adults, but few studies have addressed the impact of children’s own HL on their weight and lifestyle. In this study, we aim to assess the impact of Dutch children’s HL on (1) their BMI z-score, (2) dietary behaviour, and (3) the amount of physical activity (PA) they engage in. A sample of 139 children (age 8–11 years) filled out a digital questionnaire,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
2
6
1
Order By: Relevance
“…With regards to our second research question, this study extends current understanding of the association between child health literacy and a range of developmental outcomes using multiple health literacy assessment tools [ 44 , 45 , 46 ]. Consistent with previous findings [ 14 , 71 , 72 , 74 , 81 , 82 ], we found that high health literacy in children was associated with a series of positive outcomes, including more health-promoting behaviours, lower BMI, frequent patient-provider communication, better health status, higher HRQoL, and higher academic performance. However, the magnitude of associations varied by each health literacy assessment tool.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…With regards to our second research question, this study extends current understanding of the association between child health literacy and a range of developmental outcomes using multiple health literacy assessment tools [ 44 , 45 , 46 ]. Consistent with previous findings [ 14 , 71 , 72 , 74 , 81 , 82 ], we found that high health literacy in children was associated with a series of positive outcomes, including more health-promoting behaviours, lower BMI, frequent patient-provider communication, better health status, higher HRQoL, and higher academic performance. However, the magnitude of associations varied by each health literacy assessment tool.…”
Section: Discussionsupporting
confidence: 91%
“…The present study used multiple health literacy assessment tools to investigate the patterning of health literacy by socio-demographic and individual characteristics and quantify the impact of different measurement approaches on developmental outcomes among Chinese secondary school students. Confirmed with previous findings [ 14 , 19 , 71 , 72 , 73 , 74 ], we found that health literacy was associated with a range of upstream factors and developmental outcomes in children, no matter which approach was used to measure health literacy. Different health literacy assessment tools provide varying specificity for quantifying population socio-demographics, individual characteristics, and developmental outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…However, not all of the studies have indicated a significant association between HL and anthropometrics/body composition. For example, a study on children aged 8–11 years did not find a significant correlation between HL and body mass index, which was explained by the limited variation in body mass index, as most of the children were within the normal range [ 46 ]. We can offer a similar explanation for the lack of association between HL and body-build indices in our research.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, a study on Finnish adolescents aged 13–15 reported that adolescents with higher HL levels were more likely to participate in sports activities, leading to increased PAL [ 59 ]. Moreover, a study on 8–11 year-old children from the Netherlands recorded a strong positive relationship between HL and PAL; children with higher HL had higher PAL [ 60 ]. Meanwhile, we did not record a correlation between PAL and HL.…”
Section: Discussionmentioning
confidence: 99%